Silicon anode in lithium-ion batteries - Roper, IPE (2019)
In this thesis we consider the chemo-mechanical response of a multi-material lithium-ion battery anode nano-particle at equilibrium. The stresses are induced by lithium being intercalated into the nano-particle, causing the anode materials to expand. The presence of several anode materials expanding to different extents induces stress even at equilibrium. The model we primarily study is a linear elasticity model derived under the assumption that the stress-free expansion of each anode material is small. We couple the mechanical model to a diffusion-based model governing the transport of lithium in each material through stress-assisted diffusion. At equilibrium, the chemical potential of the lithium, which depends both on the lithium concentration and the hydrostatic stress, is uniform throughout the nano-particle, governing the distribution of lithium between the materials.